The Causal Effect of Unemployment Duration on Wages: Evidence from Unemployment Insurance Extensions - Johannes F. Schmieder; Till von Wachter; Stefan Bender (Institute for the Study of Labor (IZA), 2014)
This paper estimates the causal effect of long-term unemployment on wages. Job search theory implies that if Unemployment Insurance (UI) extensions do not affect wages conditional on the month of unemployment exit, then reservation wages do not bind on average. Then, UI extensions affect mean wages only through unemployment durations and are valid instrumental variables (IV). Using a regression discontinuity design, we find that UI extensions in Germany reduced job searchers' reemployment wages on average, but did not affect wages conditional on unemployment duration. Resulting IV estimates imply substantial negative effects of unemployment duration on wages of 0.8% per month.
Keywords: J64; J65; 330; long-term unemployment; wage losses; unemployment insurance